696 Moderate sedation for transesophageal echocardiography guidance of percutaneous left atrial appendage closure: the MID-DEX protocol. (8th December 2021) - Sanfilippo, Maria; Vizzari, Giampiero; Giacchi, Giuseppe; Mancini, Nastasia; Allegra, Marta; Mazzone, Paolo; Laterra, Giulia; Sacchetta, Giorgio; Micari, Antonio; Contarini, Marco
Abstract: Aims: Left atrial appendage closure (LAAC) is usually performed under general anesthesia to allow prolonged transesophageal echocardiography (TEE) guidance. There is scarce knowledge about the feasibility and safety of moderate conscious sedation (MCS) in LAAC. We aimed to assess the feasibility, effectiveness and safety of an innovative MCS protocol of dexmedetomidine plus midazolam (MID-DEX), in a retrospective population of LAAC patients. Methods and results: A total of 100 patients underwent LAAC with MCS using the MID-DEX protocol between May 2019 and January 2021 in a single centre. Clinical and procedural outcomes of these patients have been collected in the context of a retrospective registry on LAAC with the Watchman FLX device. All patients were treated preoperative with Dex, administered with initial bolus infusion (1.0 mcg/kg) in 10 min, then i.v. infusion was maintained throughout the LAAC procedure (0.2–1.0 μg/kg/h), tailored on patient's frailty (advanced age, low body mass index) and haemodynamic status (BP, HR). Midazolam was administered to patients after Dex bolus, to induce sedation and to ease probe insertion, according to patient age and respiratory status (from 2.5 to max 10 mg). The ease of insertion of the TEE probe (one very easy—five impossible), and the duration of the TEE (m′) were recorded. Additional variables were: total amount of each drug given, time to recovery from sedation. After procedure a verbal survey about the quality of sedation, level of comfort, recall of the procedure, and future acceptance of this type of sedation was administered. The operators also rated the procedural conditions on a scale of 1–5 (5 = excellent). Mean patient age was 78.5 ± 6.96 years and 34% were women. The mean LVEF was 62.9 ± 8.9%. All patients underwent LAAC under MID-DEX MCS protocol with an acute procedural success rate of 100%. Ninety patients (90%) successfully underwent TEE under MCS; in 10 patients ICE guidance was required. Fluoroscopic time was 31 ± 21.7 min. The median required dosage of Dex infusion was 0.08–0.09 μg/kg/h and midazolam was 6.2 ± 2.4 mg. No complications were observed from MCS. There was no need for conversion to GA during the procedure. We observed five cases of bradycardia (solved by reducing to half Dex infusion) and three of hypotension (only two requiring Ringer's solution infusion). Echocardiographist rated procedural conditions as perfect (5) in 85% of cases and good (4) in 6%. Interventionalist rated procedural comfort with 5 (excellent) in 90% of cases and 4 (good) in 3%. Patients satisfaction was high with best rate (5) in 80% with 5% of 4 (good); 12% described the procedure as fair, without memory of discomfort. Conclusions: LAAC is safe and effective when performed under MCS. Thus, applying MCS may simplify the LAAC procedure, as well as reduce procedural time and procedural costs, while increasing overall patient and physician satisfaction.